2013
DOI: 10.1016/j.jpeds.2013.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding during Indomethacin and Ibuprofen Treatment of a Patent Ductus Arteriosus

Abstract: Objective To test the hypothesis that infants who are just being introduced to enteral feedings will advance to full enteral nutrition at a faster rate if they receive “trophic” (15 ml/kg/day) enteral feedings while receiving indomethacin or ibuprofen treatment for patent ductus arteriosus (PDA). Study design Infants were eligible for the study if they were 231/7 – 306/7 weeks gestation, weighed 401–1250 g at birth, received maximum enteral volumes ≤60 ml/kg/day and were about to be treated with indomethacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 20 publications
1
39
1
1
Order By: Relevance
“…A study by Clyman et al in 177 premature infants comparing trophic feeds at 15 mL/kg/day versus no feeds during indomethacin or ibuprofen PDA treatment reported that infants fed during treatment required 3 to 4 fewer days to reach 120 mL/kg/day of enteral feeds without evidence of increased feeding intolerance or increased SIP or necrotizing enterocolitis. 11 Our study in contrast to that of Clyman et al examined prophylactic rather than therapeutic indomethacin in relation to early enteral nutrition. We did not examine the interaction of ibuprofen and early enteral feeding concerning SIP.…”
Section: Figurementioning
confidence: 73%
See 3 more Smart Citations
“…A study by Clyman et al in 177 premature infants comparing trophic feeds at 15 mL/kg/day versus no feeds during indomethacin or ibuprofen PDA treatment reported that infants fed during treatment required 3 to 4 fewer days to reach 120 mL/kg/day of enteral feeds without evidence of increased feeding intolerance or increased SIP or necrotizing enterocolitis. 11 Our study in contrast to that of Clyman et al examined prophylactic rather than therapeutic indomethacin in relation to early enteral nutrition. We did not examine the interaction of ibuprofen and early enteral feeding concerning SIP.…”
Section: Figurementioning
confidence: 73%
“…[15][16][17] A case-control study 8 and a randomized controlled trial 11 18 provides prospective longitudinal data pertaining to both indomethacin treatment within the first 24 hours after birth for any indication and the occurrence and timing of SIP. The primary hypothesis was that in ELBW infants, concomitant prophylactic intravenous indomethacin within the first 24 hours after birth, and any enteral feeding within the first 3 days after birth would be associated with a $20% increased relative risk of SIP during the first 14 days after birth compared with those who received prophylactic indomethacin but no feeding within the first 3 days after birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] A case-control study 8 and a randomized controlled trial 11 have shown that enteral feeding concurrent with treatment of a PDA with indomethacin results in fewer days to reach full enteral feeds without evidence of increased feeding intolerance or increased SIP or necrotizing enterocolitis. The question of whether ELBW infants who receive prophylactic indomethacin should concurrently receive enteral nutrition or have their feeds withheld temporarily because of the risk of SIP remains unanswered.…”
Section: Discussionmentioning
confidence: 99%